The initial stage of geological development of the continental Earth's crust in the territory of Ukraine in Dokatarhey-Archean - Yesypovych, Stanislav (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2016)
This paper contains a diagram of ring structures within the territory of Ukraine from the point of view of the classical idea elaboration on forming the dawn of continental crust on the ooidno-ring stage of planet evolution. This diagram is a development of O.B. Gintov concept about tectonic co-centers as structures with stable nuclei and mobile ring frames. The attention draws to intersection/overlay zones, as critical geodynamic areas of the Earth’s crust.